Effect of mebendazole and praziquantel on glucosephosphate isomerase and glyceraldehydephosphate dehydrogenase in Echinococcus granulosus cyst wall harbored in mice - You Ji-Qing; Xiao Shu-Hua; Guo Hui-Fang; Jiao Pei-Ying; Mei Jin-Yan; Yao Min-Yi (Acta Pharmacologica Sinica; Vol 18, No 1 (January 1997): Acta Pharmacologica Sinica, 2016)
AIM: To study effects of antihydatid drugs on glucosephosphate isomerase (GPI) and glyceraldehydephosphate dehydrogenase (GAPDH) in Echinococcus granulosus cyst wall. METHODS: Mice infected with the parasite for 8-10 months were treated i.g. with mebendazole (Meb) or praziquantel (Pra). The activities of GPI and GAPDH in the cysts were measured by the formation of NADH or NADPH. RESULTS: GPI activity in the cyst wall was 197 +/- 103 U, while that of GAPDH was 25 +/- 13 U. When infected mice were treated i.g. with Meb 25-50 mg.kg-1.d-1 for 7-14 d, no apparent effect on the GAPDH activity in the cyst was found. In mice treated i.g. with praziquantel (Pra) 500 mg.kg-1.d-1 for 14 d, the GAPDH activity in the cyst wall was inhibited by 26.5%. As to GPI activity only the group treated i.g. with Meb 25 mg.kg-1.d-1 for 14 d showed 33.2% inhibition of the enzyme in the collapsed cyst wall. CONCLUSION: GPI and GAPDH are not the major targets attacked by the antihydatid drug.